A sense of place using visual characteristic in historic city - Ismail, Noratiah; Nik Mohammad, Nik Mastura; Mohd Ariffin, Noor Fazamimah; Ismail, Sumarni (Science Publishing Corporation, 2019)
Recognising the transition of the values associated to urban heritage conservation will open the way to the definition of the present and future value system. The Historic Urban Landscape is the urban area understood as a historic layering of cultural and natural values, extending beyond the notion of ‘historic centre’ or ‘ensemble’ to include the broader urban context and its geographical setting (UNESCO, 2011). This research looks at the theory of ˋsense of placeˊ and how ˋvisual elementsˊ play important roles in creating a sense of place in historic urban area. Steele (1981) suggested that ˋsense of placeˊ is justified by individual experience of a person in a particular setting. It is a mixture of significant physical, social and cultural elements in a place that has shaped the unique and distinctive characteristic of the place. Christian Norberg-Schulz emphasized on the notion of the relationship of culture and buildings (physical elements) in sense of place. This connection could be interpreted by assessing the visual elements of the place. The study explores on how urban landscape of a historic setting could serve as the evidence for ˋsense of placeˊ that formed the identity of the area. Assessment made regarding the connection of physical and socio-cultural elements of the place could serve as an indication of sense of place. The visual evidence of the area provides information on how these elements work and interact. These interactions will be assessed through a set of indicators which were produced based on a number of studies carried out concerning ˋsense of place.ˊ The indicators are used to evaluate how a place identity is visually remembered as in the visual dimension impact (VDI). VDI often relates to significance of memory of the setting of the place based on its characteristics and special elements such places are remembered, hence the sense of place. The design and usage of spaces of a townscape create this unique characteristic thus the visual dimension impact of the place.